Immunogenic sonodynamic therapy for inducing immunogenic cell death and activating antitumor immunity - Wang, Ting; Peng, Wangrui; Du, Meng; Chen, Zhiyi (Frontiers in Oncology, 2023)
Immunotherapy is widely regarded as a promising treatment for cancer. However, the immune effector phase suppression of tumor microenvironment (TEM) and the generation of immune-related adverse events (irAEs) limit its application. Recently, more and more evidence indicates that sonodynamic therapy (SDT) can effectively activate anti-tumor immunity while killing tumor cells. SDT can produce cytotoxic substances of tumors, and then cell apoptosis and immunogenic death occurred by selectively activating the sonosensitizer under ultrasound. In recent years, various SDT alone as well as SDT in combination with other therapies have been developed to induce immunogenic cell death (ICD) and enhance cancer immunotherapy. This paper overviews the research progress of SDT and nanotechnology in recent years, including the strategies involving SDT alone, SDT-based synergistic induction of anti-cancer immunity, and Immunotherapy in basis of SDT for multimodal immunotherapy. Finally, the prospects and challenges of these SDT-based therapies in cancer immunotherapy are discussed.